CHEMICAL CHARACTERISTIC AND ANTIOXIDANT ACTIVITY OF METHANOL EXTRACT NEEM LEAVES (AZADIRACHTA INDICA JUSS) - Supriyanto, Supriyanto; Widjanarko, Simon Bambang; Rifa'i, Muhaimin; Yunianta, Yunianta (AGROINTEK, 2021)
The neem plant (Azadirachta indica) is a herb with the potential as a source of antioxidants. This study aimed to identify compounds that exist in the neem leaf and determine their antioxidant activity. Neem leaf extract was collected by using 80% methanol. Â Furthermore, methanol extracts from neem leaves with the highest antioxidant activity were partitioned with n-hexane, ethyl acetate, and water. This research were analyzed by partition for antioxidant activity, and DPPH (1,1-diphenyl-2-pycrilhydrazil) and the half-maximal inhibitory concentration (IC50) values were determined. The results showed that the ethyl acetate partition had the highest antioxidant activity, with IC50 values of 1.004 Âµg/ml. Neem leaf extract has the potential for a use as an herbal medicine in the treatment of various diseases..